1964
DOI: 10.1530/jrf.0.0070357
|View full text |Cite
|
Sign up to set email alerts
|

Antigenicity and Cross-Reactions of Bovine Spermatozoa

Abstract: Summary. The antigenicity and cross-reactions of bovine seminal constituents were studied using complement fixation, agar-gel-diffusion, and immuno-electrophoresis. Bovine

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

1967
1967
1987
1987

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 7 publications
1
20
0
Order By: Relevance
“…Hunter & Hafs (1965) reported that rabbit semen contained nine antigens, seven common to seminal plasma and two specific for spermatozoa. These same authors (Hunter & Hafs, 1964) found that bull spermatozoa possessed at least seven antigens of which five were shared with seminal plasma and one with blood serum.…”
Section: Introductionmentioning
confidence: 93%
“…Hunter & Hafs (1965) reported that rabbit semen contained nine antigens, seven common to seminal plasma and two specific for spermatozoa. These same authors (Hunter & Hafs, 1964) found that bull spermatozoa possessed at least seven antigens of which five were shared with seminal plasma and one with blood serum.…”
Section: Introductionmentioning
confidence: 93%
“…Procedures for the Ouchterlony technique and immuno-electrophoresis were identical to those described by Hunter & Hafs (1964).…”
Section: Introductionmentioning
confidence: 99%
“…Ouchterlony precipitation in gel techniques were described previously (Hunter & Hafs, 1964 Hunter & Nornes (1969). BSV suspension (0-5 ml, 6 mg protein) was eluted from the column (IT cm 52 cm) at the rate of 2-6 ml/cm2/hr at room temperature.…”
Section: Introductionmentioning
confidence: 99%